2020
DOI: 10.1002/nano.202000084
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical charge transfer for high‐performance triboelectric nanogenerators

Abstract: Triboelectric nanogenerators (TENGs) provide the most effective technology for using distributed mechanical energy to power distributed sensor networks. Improving the surface charge density is important to optimizing the performance of TENGs. Unlike electrets with steady-state charges, there is a changing chargedischarge process in the working cycle for materials for TENGs. This article reviews several mechanisms to improve surface charge density by using decay coefficient, transfer time, and effective charge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
(223 reference statements)
0
19
0
Order By: Relevance
“…This leads to a rapid decay in the surface charge and the potential difference. [36][37][38][39][40][41] Therefore, to prevent the combination of the charge during HVCI, it is important to confine the drifting charge before it is lost in the electrode. Further, the transport process of incoming charges to the deep position close to the electrode is important because remaining charges that cannot be transported on the surface interfere with the inflow of new charges due to repulsion by the same type of charge during HVCI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a rapid decay in the surface charge and the potential difference. [36][37][38][39][40][41] Therefore, to prevent the combination of the charge during HVCI, it is important to confine the drifting charge before it is lost in the electrode. Further, the transport process of incoming charges to the deep position close to the electrode is important because remaining charges that cannot be transported on the surface interfere with the inflow of new charges due to repulsion by the same type of charge during HVCI.…”
Section: Resultsmentioning
confidence: 99%
“…[35] However, a recent study examining dynamic charge transfer found that when a charge is induced between a contact surface and an electrode, the charge on the surface drifts due to the combination of the induced electric field with the opposite charge in the electrode, thus causing the charge on the surface to be lost. [36][37][38][39][40][41] Further, the charge remaining on the surface inhibits the entry of new charges, which makes it hard to achieve a high surface charge density, thereby decreasing the potential difference. Therefore, in the design of high-performance TENGs, it is critical to transport the charge on the surface to a deep position while reducing charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Generally, part of the surface charges will be consumed by the widespread existence of leakage current in dielectric film [ 21 ] and air breakdown effect. [ 22,23 ] The common TENG will quickly reach a low equilibrium state between the charge accumulation and charge decay ( Figure 1a (i)) due to the inevitable degradations and limited surface charges generated by triboelectrification, accompanied by a low output performance. [ 20,24 ] To increase the charge density, some efforts, e.g., high vacuum environment [ 25 ] and high‐pressure gas environment, [ 26 ] have been devoted to suppressing the surface charge decay by avoiding air breakdown in a high surface charge density state (Figure 1a (i)).…”
Section: Introductionmentioning
confidence: 99%
“…2a-c. Such improvement could be rationalized in terms of the net charge transferred between the triboelectric materials (DQ sc ), which could be written as: [53][54][55][56]…”
Section: Introductionmentioning
confidence: 99%
“…2a–c. Such improvement could be rationalized in terms of the net charge transferred between the triboelectric materials (Δ Q sc ), which could be written as: 53–56 where C 0 is the capacitance at the triboelectric interface, V c is the contact potential difference between two triboelectric layers, and ϕ d and ϕ e is the effective WF of the dielectric layer and electrode layer, respectively. This equation indicates that a larger WF difference between the triboelectric materials favors the generation of triboelectric charges.…”
Section: Introductionmentioning
confidence: 99%